Apoptosis-mediated inhibition of human T-cell acute lymphoblastic leukemia upon treatment with Staphylococus Aureus enterotoxin-superantigen - Duarte, Alejandra; Montagna, Daniela R.; Pastorini, Mercedes; Alemán, Mercedes (Frontiers in Immunology, 2023)
Patients with relapsed T cell acute lymphoblastic leukemia (T-ALL) have limited therapeutic options and poor prognosis. The finding of efficient strategies against this refractory neoplasm is a medical priority. Superantigens (SAgs) are viral and bacterial proteins that bind to major histocompatibility complex class II molecules as unprocessed proteins and subsequently interact with a high number of T cells expressing particular T cell receptor Vβ chains. Although on mature T cells, SAgs usually trigger massive cell proliferation producing deleterious effects on the organism, in contrast, on immature T cells, they may trigger their death by apoptosis. On this basis, it was hypothesized that SAgs could also induce apoptosis in neoplastic T cells that are usually immature cells that probably conserve their particular Vβ chains. In this work, we investigated the effect of the SAg Staphylococcus aureus enterotoxin E (SEE) (that specifically interacts with cells that express Vβ8 chain), on human Jurkat T- leukemia line, that expresses Vβ8 in its T receptor and it is a model of the highly aggressive recurrent T-ALL. Our results demonstrated that SEE could induce apoptosis in Jurkat cells in vitro. The induction of apoptosis was specific, correlated to the down regulation of surface Vβ8 TCR expression and was triggered, at least in part, through the Fas/FasL extrinsic pathway. The apoptotic effect induced by SEE on Jurkat cells was therapeutically relevant. In effect, upon transplantation of Jurkat cells in the highly immunodeficient NSG mice, SEE treatment reduced dramatically tumor growth, decreased the infiltration of neoplastic cells in the bloodstream, spleen and lymph nodes and, most importantly, increased significantly the survival of mice. Taken together, these results raise the possibility that this strategy can be, in the future, a useful option for the treatment of recurrent T-ALL.